Bupivacaine-Induced Kounis Syndrome - Efe YILMAZ; Çağlar KAYA (Namık Kemal Tıp Dergisi)
Bupivacaine is frequently used in daily practice for local anesthesia. The cardiotoxic and arrhythmic effects of bupivacaine are known. Acute allergic attacks and electrocardiographic changes associated with bupivacaine have not been reported in the literature. Kounis syndrome presents with the clinical picture of acute myocardial infarction following an acute allergic attack. Coronary angiography was planned for the patient, who had a known coronary artery bypass graft, with the diagnosis of unstable angina pectoris. After subcutaneous bupivacaine injection applied to the radial area, severe chest pain and electrocardiography changes occurred. No acute occlusive lesion was detected in coronary angiography. In this article, bupivacaine-associated kounis syndrome will be presented.